2011
DOI: 10.1111/j.1365-2656.2011.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Life in varying environments: experimental evidence for delayed effects of juvenile environment on adult life history

Abstract: Summary1. The effects of environment experienced during early development on phenotype as an adult has started to gain vast amounts of interest in various taxa. Some evidence on long-term effects of juvenile environment is available, but replicated experimental studies in wild animals are still lacking. 2. Here we report the first replicated experiment in wild mammals which examines the long-term effects of juvenile and adult environments on individual fitness (reproduction, survival and health). The early dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…This effect was again mediated by reproduction, which although marginal, was clearly more prevalent in food supplemented than nonsupplemented populations. This finding is consistent with previous research that has shown high quality food resources to facilitate winter reproduction in voles (Kaikusalo and Tast 1984), as well as advance the onset of spring reproduction (Taitt and Krebs 1981, Haapakoski et al 2012, Helle et al 2012.…”
Section: During Winter (Iii Iv)supporting
confidence: 82%
See 1 more Smart Citation
“…This effect was again mediated by reproduction, which although marginal, was clearly more prevalent in food supplemented than nonsupplemented populations. This finding is consistent with previous research that has shown high quality food resources to facilitate winter reproduction in voles (Kaikusalo and Tast 1984), as well as advance the onset of spring reproduction (Taitt and Krebs 1981, Haapakoski et al 2012, Helle et al 2012.…”
Section: During Winter (Iii Iv)supporting
confidence: 82%
“…A common line of differentiation is between intrinsic (for example age structure and maternal or juvenile environment: see [60][61][62][63]) and extrinsic factors (the environment, including predation: see [6,9]. However, recent transplant experiments have provided compelling evidence to support an important effect of the immediate environment on the life history traits of voles [64][65] (see however [63]). Our identification of diet quality limitation on increasing vole populations is consistent with the latter findings.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one main function of mitochondria is to couple respiration (i.e. O 2 consumption) and nutrient oxidation to ATP synthesis, but interestingly, this coupling (also defined as mitochondrial efficiency) demonstrates a certain degree of plasticity (Brand, 2000;Divakaruni and Brand, 2011;Helle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These individual differences allow for variation in diet among individuals exposed to the same local conditions. Past events can influence the current state of individuals and alter their feeding needs and diets (Beckerman et al 2002, Ehrlen 2000, Helle et al 2012, Tanner et al 1996, Tanner et al 2011. Also, variation in prey in local environments can affect among-individual variation in consumers (Matthews and Mazumder 2004).…”
Section: List Of Tablesmentioning
confidence: 99%
“…All niche-use theories assume that past conditions at a site affect current conditions, and are the basis for predicting future actions of individuals (Beckerman et al 2002, Ehrlen 2000, Helle et al 2012, Tanner et al 1996, Tanner et al 2011. However, among mobile species inhabiting landscapes with multiple 'sites,' a simple alternative explanation for among-individual variation is that diet resources differed in the environments from which they dispersed (Tilman 1994).…”
Section: List Of Tablesmentioning
confidence: 99%